(untitled) (Journal of Coating Science and Technology, 2017)
The paper studies the possibility of superhydrophobic coatings formations at exposure of powder mixture of polytetrafluorethylene and hydrocarbons having various molecular weights to low-energy electron beam in vacuum. It is shown that paraffin and PTFE based thin composite coatings may be characterized by superhydrophobic properties. The superhydrophobic properties are attained due to low surface energy of the fluorine-containing component and structured surface due to peculiarities of composite layer formation. The chemical processes observed in electron beam exposed area determine the molecular structure, morphology and the contact angle of thin organic coatings deposited. It is shown that high-molecular-weight hydrocarbon compounds should not be recommended for vacuum electron-beam deposition of superhydrophobic thin coatings because of deep changes in the molecular structure exposed to electron beam. These processes are responsible for high degree of unsaturation of the thin layer formed and for occurrence of oxygen-containing polar groups. The influence of substrate temperature on molecular structure, morphology and hydrophobic properties of thin coatings deposited is investigated. Potentially such coatings may be applied for deposition on the surface of metal capillaries used in biotechnological analyzers.